PLC based automatic grinding system for door frames - Rohith Mervin, Noel; R, Aravind; Joe S, Bestley (International Journal of Engineering and Technology, 2018)
Usually in order to smoothen or flatten any surface we generally prefer grinding process, the grinding process can be done in surface area or metal portion in any possible areas or metal portion in any possible area we want. This research work is on automation, since automation can be done for grinding of door frames. This idea gained inertest is due to the increasing demand of door frames for the customers in huge amount of production rates. There are several methods to grind the door frames either it can be done by humans (man-made), because normally grinding is a process which is being done manually by humans and we also have several methods other than manual grinding techniques. By automation using â€œprogrammable logic controllersâ€Â  (PLC) which can overcome the traditional relay logic controllers, the door frames can be preferably grinded in a fraction of seconds and production rates to gets higher. Since we use (PLC) being the industrial tool, it performs the step-by-step sequence combined by both mechanical and electrical parts. In this paper, theÂ  proposed (PLC) based grinding automation is performed and finally compared with the conventional methods being used before grinding process and validated by using real time status obtained.Â Â